Delivering peritoneal dialysis for the multimorbid, frail and palliative patient. Issue 3 (May 2020) - Brown, Edwina A; Hurst, Helen
Peritoneal dialysis (PD) is only one component of care for older multimorbid, frail and/or palliative patients. Goals of care should be determined for all patients by shared decision-making at the start of during time on PD. Burden of PD should be minimized by individualizing the prescription by allowing for residual renal function and tailored to what is acceptable to the patient. PD facilities should develop the care pathways needed for this group of patients including integration with local geriatric, palliative care and social services